Challenges of Gender-Responsive Pedagogy Practices of Teachers - Donna Claire C. Reynales; Lehai B. Beloro (Future Science / FSH-PH Publications, 2026)
The study aimed to determine the influence of challenges on gender-responsive pedagogy (GRP) practices at Central Bicol State University of Agriculture-Sipocot Campus during the school year 2024-2025. This employed a descriptive-correlational method. Statistical analyses included weighted mean, Pearson Product- Moment Correlation Coefficient, and Coefficient of Determination. The data show that teachers are generally in agreement on the issues they face, with an average weighted mean (AWM) of 3.02. Despite challenges, GRP practice was very high, with an average weighted mean (AWM) of 3.65, indicating